MOTIVASI MEMBELI PRODUK PEMUTIH WAJAH PADA REMAJA PEREMPUAN - Maria Sriyani Langoday; Flora Grace Putrianti (Universitas Sarjanawiyata Tamansiswa, 2015)
AbstractÂ The purpose of this study is to determine the relationship of self-concept and motivation to buy whitening products among girls.Subjects in this study were young woman using cosmetic whitening facial at the University Sarjanawiyata Tamansiswa Yogyakarta. The sampling technique was purposive sampling with the Product Moment Correlation analysis method.The results of the self-concept of variable data with the motivation to buy whitening products shows the value of (r) 0.725 with P = 0.000 (P <0.01). Based on the results of the analysis can be stated that the hypothesis is accepted. This means that self control variables contribute effectively to the motivation to buy whitening products by 52.5% and 47.5%. Influenced by other factors.Â Keywords: Motivation Buy Face Whitening Products, Self Concept.